2021
DOI: 10.3390/biology10090892
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Resistance against Early Blight Introgressed in Potato

Abstract: Early blight is a disease of potato that is caused by Alternaria species, notably A. solani. The disease is usually controlled with fungicides. However, A. solani is developing resistance against fungicides, and potato cultivars with genetic resistance to early blight are currently not available. Here, we identify two wild potato species, which are both crossable with cultivated potato (Solanum tuberosum), that show promising resistance against early blight disease. The cross between resistant S. berthaultii a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Based on previous studies on A. solani , we selected a relatively stable housekeeping gene " Actin " as an internal reference gene [ 24 , 25 ]. Specific primers for Actin and AsCEP112 were designed using the National Center for Biotechnology Information (NCBI) database ( https://www.ncbi.nlm.nih.gov/ ) (Supplementary Table S 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies on A. solani , we selected a relatively stable housekeeping gene " Actin " as an internal reference gene [ 24 , 25 ]. Specific primers for Actin and AsCEP112 were designed using the National Center for Biotechnology Information (NCBI) database ( https://www.ncbi.nlm.nih.gov/ ) (Supplementary Table S 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Early blight is an important disease of tomato and potato that is caused by the necrotrophic fungal pathogen Alternaria solani (52-54). In a previous study, we found a wild potato species, Solanum commersonii , with strong resistance to A. solani (55). We showed that resistance is likely caused by a single dominant locus and that it can be introgressed in cultivated potato (55).…”
Section: Introductionmentioning
confidence: 97%
“…Resistance to necrotrophs is usually considered to be a complex, polygenic trait, or recessively inherited according to the inverse gene-for-gene model (56)(57)(58)(59)(60)(61). It therefore surprised us to find a qualitative dominant resistance against early blight in S. commersonii (55).…”
Section: Introductionmentioning
confidence: 99%
“…In these previous studies, resistance levels showed a continuous distribution, suggesting that there were no dominant resistance genes for early blight resistance in these populations. However, Wolters et al (2021) recently found early blight dominant genetic resistance from the cross between S. commerosum subp. malmeanum and diploid S. tuberosum.…”
Section: Introductionmentioning
confidence: 99%